2020
DOI: 10.1186/s12905-020-01030-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between bidirectional Stratafix® barbed suture and conventional suture in laparoscopic myomectomy: a retrospective study

Abstract: Background Laparoscopic myomectomy (LM) is one of the techniques feasible for the treatment of intramural myoma. This technique is reported to be difficult when large fibroids are involved because of excessive blood loss during surgery. Skillful and fast suturing appears to be associated with reduced blood loss during LM. In this study we compared the surgical outcomes of using bidirectional Stratafix® barbed suture versus conventional suture during LM. Methods This ret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Our results show that use of BS in ovarian MCT resection by LESS leads to a significantly shorter time in suturing the ovarian cortex and overall operation time compared with CS, suggesting that BS provides higher operative efficiency. Our findings were consistent with previous studies of conventional laparoscopic myomectomy or vaginal cuff suturing that also found that the use of BS reduces operative time compared with CS 18,19 . In particular, the obvious improvement to suturing and knotting efficiency associated with BS is attributable to bypassing the requirement of knots at the beginning and end of suturing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results show that use of BS in ovarian MCT resection by LESS leads to a significantly shorter time in suturing the ovarian cortex and overall operation time compared with CS, suggesting that BS provides higher operative efficiency. Our findings were consistent with previous studies of conventional laparoscopic myomectomy or vaginal cuff suturing that also found that the use of BS reduces operative time compared with CS 18,19 . In particular, the obvious improvement to suturing and knotting efficiency associated with BS is attributable to bypassing the requirement of knots at the beginning and end of suturing.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were consistent with previous studies of conventional laparoscopic myomectomy or vaginal cuff suturing that also found that the use of BS reduces operative time compared with CS. 18,19 In particular, the obvious improvement to suturing and knotting efficiency associated with BS is attributable to bypassing the requirement of knots at the beginning and end of suturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a bidirectional barbed suture during laparoscopic myomectomy is related to a faster suturing technique. Therefore, the myometrium remains open for less time during the procedure, which may reduce intraoperative bleeding [15 ▪▪ ].…”
Section: Barbed Suturementioning
confidence: 99%
“…Another retrospective study [15 ▪▪ ] compared the bidirectional barbed suture (Stratafix, Ethicon Inc., USA) with a conventional suture (Vicryl, Ethicon Inc., USA) during laparoscopic myomectomy with regard to surgical outcomes. This study included 44 patients between April 2015 and June 2020, with 29 patients in the barbed suture group and 15 patients in the conventional suture group.…”
Section: Barbed Suturementioning
confidence: 99%